STEAM SYSTEM OPTIMIZATION AT PALM OIL MILL : CASE STUDY IN SABAH, MALAYSIA - SITTI AISHAH, NAJAMUDIN (Universiti Malaysia Sarawak, (UNIMAS), 2019)
System optimization is the method to identify the amount of saving achievable to ensure the equipment used throughout the mill is operated in an optimum condition. Steam system optimization (SSO) in this study is being conducted at the palm oil mill, Sabah. The problem being addressed in this study is low temperature of feedwater boiler which in the range of 55℃ to 65℃ and the temperature of the steam to sterilize the fresh fruit bunches (FFB) also low. This problem probably because of an inefficient configuration of the mill’s steam system and the boiler efficiency only 68.6%. Therefore, the objectives of this research are the current condition of the mill needs to be scrutinized in order to modify the system back to its initial best efficiency, investigate the energy baseline, its productions output, identifying various losses and its cost impact to the mill. On-site measurement has been carried out in order to evaluate the steam system at the mill and do the qualitative analysis. The measurement consists of office data collection, heat losses measurement and stack gas measurement. The energy baseline and the productions output within three years obtained from the office data collection from 2016 to 2018. The software used to evaluate the results of the measurement is 3E Plus: Insulation Program Software and the Steam System Assessment Tool (SSAT). The approximate model of the real steam system has been generated using SSAT. The estimation of total heat losses through the insulation evaluation is around 95.0 kW for every second during the process of FFB and equivalent around MYR 13 221.00 per year that being wasted. Through the evaluation of the current operating steam system, the percentage of blowdown losses and the stack losses are 4.9% and 26.4% respectively. The proposed SSO opportunities are installing the feedwater economizer and reduce the blowdown rate of the boiler by implementing the automatic blowdown control system. By increase, the efficiency to 77% will improve the steam quality and production output of the mill. The implication of findings are the estimated annual electrical demand saving for the mill is around 4,903 kW and also can save estimated 75,576 GJ/yr of energy demand. It also reduces 13,002 mt of carbon dioxide per annum from being exhausted into the environment. Thus, all the objectives are achieved and the estimated annual net cost savings are MYR 400,000.00 through this system optimization.